Pengaruh Kepuasan dan Kedisiplinan Kerja Terhadap Prestasi Kerja Guru SD Negeri di Kecamatan Mandai Kabupaten Maros - Firdaus Daud (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: The purpose of this expostfacto survey was to describe: influence of work satisfaction on work achievement; influence of work discipline on work achievement; influence of work satisfaction and discipline of elementary school on teachers’ work achievement. Population of the research was 314 elementary schools’ teacher at Maros Regent. Sample were drawn randomly 40%. The collected data were analysed used descriptive and inferential. Results found: (1) teachers’ satisfaction was quite good and teachers’ achievement was high. (2) more satisfaction and dsicipline teachers, higher their achievement.